Accounting quickstart guide : the simplified beginner's guide to real-world financial & managerial accounting for students, small business owners, and finance professionals / Josh Bauerle - Bauerle, Josh
Meet Josh Bauerle, reluctant accounting student turned super CPA and author of the Accounting QuickStart Guide, 3rd Edition. This revolutionary book expertly simplifies accounting fundamentals and is an invaluable resource for accounting students, business owners, bookkeepers, and other finance and record keeping professionals everywhere! Whether you are a business owner looking to boost your bottom line or an accounting student looking to boost your grade, this book will prove indispensable on your journey.